Novel mobile application for direct communication between pharmacists and patients treated with oral antineoplastic agents. (4th July 2020) - Collado-Borrell, Roberto; Escudero-Vilaplana, Vicente; Ribed, Almudena; Jiménez, Rosa Romero; Peinado, Irene Iglesias; Herranz-Alonso, Ana; Sanjurjo-Sáez, María
Abstract: Purpose: Initial experience with use of a smartphone application to enhance communication with and home monitoring of hematology/oncology patients under treatment with oral antineoplastic agents (OAAs) is described. Summary: Broad use of OAAs is changing the landscape of hematology/oncology patient care, with this form of therapy giving patients greater autonomy but also raising concerns about correct OAA administration and management of adverse effects (AEs) or interactions. Information and communication technologies, specifically mobile health technologies, are ideal tools in this new environment. A multidisciplinary team at a large hospital in Spain developed a smartphone application for patients receiving OAA therapy that consists of 5 modules or functionalities: (1) a treatment agenda, or electronic journal of patient activity, including medication use; (2) a treatment record; (3) continuous recording of vital signs (blood pressure and temperature), health-related quality of life, and AEs, with management of AEs based on an algorithm that displays different recommendations according to AE severity; (4) 2-way messaging capability; and (5) information and links to websites of interest. From June through November 2017, 37 patients downloaded and used the application. About two-thirds (68%) of the patients sent a total of 182 messages to the pharmacist on duty; 58% of the patients registered at least 1 AE. The mean time of registration of the first AE after initiation of OAA therapy was 8 days. As a result of patient use of the application, 2 emergency room visits were avoided and 3 patients were referred to a general practitioner. Conclusion: The application has allowed real-time monitoring of patients treated with OAAs. This new patient-pharmacist communication channel has facilitated the early detection of AEs, contributing to the safety of treatment and patient satisfaction with healthcare.